Rethinking mining as a development panacea: an analytical review - Mandishekwa, Robson (Springer Science and Business Media Deutschland GmbH, 2021)
Extant literature exists so far on the positive contribution of mining to economic growth. However, contrary views have also been found in the form of the ‘resource curse’ and mining-induced displacement literature. These opposing literature perspectives deserve attention when mining is pursued as a panacea for economic growth. Little, if any, attention has so far been made to bring these perspectives together. The current study, therefore, brought these views together and suggested the need to rethink mining as a panacea for growth. The study found that while most governments generally accept the contribution of mining to growth and, therefore, justify mining-induced displacement, this growth strategy leads to significant counter-effects like the resource curse, disturbances in economic activities and finally satisfaction with life. Further, effects like political instability have also been highlighted. Considering all these negative effects, the benefits espoused from mining activities may not obtain. Therefore, a very serious rethinking of mining as a strategy to stimulate economic growth is necessary.